A unique case of food restriction and OCD diagnosed as PANDAS and a review of the literature - Kentab, Amal Y.; Bassraway, Rolan (Frontiers in Psychiatry, 2026)
Pediatric autoimmune neuropsychiatric disorder associated with streptococcal infections (PANDAS) is recognized as a significant causative element in the emergence of childhood-onset obsessive-compulsive disorder (OCD) and movement disorders, including tic disorders, and choreiform movement. It is associated with various behavioral and psychiatric manifestations in children, such as separation anxiety disorder, body dysmorphic disorder, attention deficit hyperactivity disorder, and eating disorders. We describe a unique case of progressive weight loss in a previously healthy 13-year-old child who had a sudden and dramatic onset of refusal to eat, induction of vomiting, emotional liability, anxiety disorder, and OCD over 6 months following fever and pharyngitis. His workup showed an elevation of antistreptolysin O (ASO) titer with a negative throat swab. PANDAS was considered. His irritability improved after a course of antibiotics, and abatement of all symptoms and progressive weight gain occurred after a course of intravenous immunoglobulin (IVIG) followed by monthly benzathine penicillin injections. This report could help to increase awareness among physicians, highlight the importance of early diagnosis, and promote treatment of PANDAS among patients who present with a combination of eating disorders and OCD.